2006
DOI: 10.1111/j.1526-4610.2006.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Rofecoxib in the Acute Treatment of Migraine: A Randomized Controlled Clinical Trial

Abstract: Rofecoxib 25 and 50 mg and ibuprofen 400 mg were effective and generally well tolerated in the acute treatment of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 20 publications
2
28
0
2
Order By: Relevance
“…The results seen with GW406381 are comparable to those described for other COX‐2 inhibitors in the treatment of migraine [12,13,25,26]. For example, headache relief at 2 h post‐dose was reported by 54–62% of rofecoxib‐treated subjects [25,26] and 45–48% of valdecoxib‐treated subjects [13]. Whilst three‐arm studies may show a greater placebo response than two‐arm studies, the 35% response seen here is similar to the 30–34% placebo responses observed in the rofecoxib and valdecoxib studies [13,25,26], and also similar to the average placebo response of 30% used to power this study and seen in clinical trials of other analgesics in acute migraine [27].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The results seen with GW406381 are comparable to those described for other COX‐2 inhibitors in the treatment of migraine [12,13,25,26]. For example, headache relief at 2 h post‐dose was reported by 54–62% of rofecoxib‐treated subjects [25,26] and 45–48% of valdecoxib‐treated subjects [13]. Whilst three‐arm studies may show a greater placebo response than two‐arm studies, the 35% response seen here is similar to the 30–34% placebo responses observed in the rofecoxib and valdecoxib studies [13,25,26], and also similar to the average placebo response of 30% used to power this study and seen in clinical trials of other analgesics in acute migraine [27].…”
Section: Discussionsupporting
confidence: 80%
“…The results seen with GW406381 are comparable to those described for other COX-2 inhibitors in the treatment of migraine [12,13,25,26]. For example, headache relief at 2 h post-dose was reported by 54-62% of rofecoxib-treated subjects [25,26] and 45-48% of valdecoxib-treated subjects [13].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Also the selective COX‐2 inhibitors have been investigated in clinical trials. Valdecoxib 20–40 mg and rofecoxib 25–50 mg, the latter one not available on the market any more, have shown efficacy in acute migraine treatment [27–30]. Table 1 presents an overview of analgesics with efficacy in acute migraine treatment.…”
Section: Drug Treatment Of Migraine Attacksmentioning
confidence: 99%
“…In placebo‐controlled trials, however, no consistent efficacy of this procedure in the acute treatment of migraine attacks [175] or in the prevention of recurrence could be proven [176–179]. Also by expert consensus and supported by open label studies, dihydroergotamine 2 mg (nasal spray or suppositories) is recommended for severe migraine attacks [29]. The intravenous application of metamizol was significantly superior to placebo but can cause severe arterial hypotension and allergic reactions [24,180].…”
Section: Specific Situationsmentioning
confidence: 99%